The complete chloroplast genome of Parnassia wightiana (Celastraceae) - Li, Jianfang (Mitochondrial DNA B Resour, 2019)
The infrageneric relationships of the genus Parnassia were not clearly identified due to limited available genetic data. In this study, we presented the complete chloroplast genome of Parnassia wightiana for future phylogenetic study. The plastome of P. wightiana was 152,043 bp in length, with a large single-copy region (LSC) of 82,737 bp and a small single-copy region (SSC) of 19,030 bp, separated by a pair of inverted repeat regions (IRs) of 25,138 bp. It contained 134 genes, including 87 protein-coding genes, 37 tRNA genes, 8 rRNA genes, and 2 pseudogenes. The overall GC content was 37.1%, while the corresponding values in the LSC, SSC, and IR region were 35.0%, 30.8%, and 42.9%, respectively. The phylogenetic analysis supported the monophyly of Parnassia.